If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(4x + -1c) = 3a + 2c Reorder the terms: 3(-1c + 4x) = 3a + 2c (-1c * 3 + 4x * 3) = 3a + 2c (-3c + 12x) = 3a + 2c Solving -3c + 12x = 3a + 2c Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '-2c' to each side of the equation. -3c + -2c + 12x = 3a + 2c + -2c Combine like terms: -3c + -2c = -5c -5c + 12x = 3a + 2c + -2c Combine like terms: 2c + -2c = 0 -5c + 12x = 3a + 0 -5c + 12x = 3a Add '-12x' to each side of the equation. -5c + 12x + -12x = 3a + -12x Combine like terms: 12x + -12x = 0 -5c + 0 = 3a + -12x -5c = 3a + -12x Divide each side by '-5'. c = -0.6a + 2.4x Simplifying c = -0.6a + 2.4x
| -17+10b=-9b+2b | | 8+(x-5)=11 | | 3a+16+15a+50= | | x^3+14x-5=0 | | 12-(n-12)=6(n+3) | | 175m-75m+48000=50250-150 | | 0=8z-(3-z) | | Cx-Fy=L | | 1/2x+1/5=4(3/4x+4) | | 12-9(y+5)=-(1-y) | | -11+-17= | | 5+7w=15+3w | | 2(2x-2)+2(3x+8)=172 | | .85t+.15(10-t)=8.7 | | 7d+d+1= | | 3-2x+4+6=9 | | 10-(n-10)=5(n+3) | | 2(2x-2)+2(3x-8)=172 | | 1/4+x=-3/4 | | 1-1/5x=-4/5(5+x) | | -3+4k=3-6+3k | | 6x^2+2y=9xy-7 | | 2x=2(2+x) | | -5/6+2/5 | | 24-21/2=x | | (2x-2)+(3x-8)=172 | | 2n+9=6n | | 16f=15f+2 | | -10x^2-65x-75=0 | | 10-3r+5+2r= | | h(t)=V*t-16*t^2 | | x-(x+17)=2(11-3x) |